Lanthanum Chloride Catalysed By Expeditious Synthesis of Azlactone Derivatives - K. F. Shelke, (International Journal of Scientific Research in Science and Technology, 2025)
The highly efficient Erlenmeyer synthesis of 4-arylidene-2-phenyl-5(4)-oxazolones (Azlactone) derivatives via the condensation of aromatic aldehydes and hippuric acid in acetic anhydride with good to excellent yield catalyzed by lanthanum chloride (LaCl3) under microwave irradiation. The present approach has several benefits, such as a simple and fast methodology that produces clean reaction profiles, short reaction times, and an easy work-up process.
Keywords: Azlactone; Lanthanum chloride; Aldehyde; Hippuric acid